KPC-Producing Enterobacter cloacae Transfer Through Pipework Between Hospital Sink Waste Traps in a Laboratory Model System. (October 2020) - Aranega Bou, Paz; Ellaby, Nicholas; Ellington, Matthew; Moore, Ginny
Abstract : Background: Carbapenemase-producing Enterobacterales (CPE) have become an increasingly common cause of hospital-acquired infections while their reservoirs within the clinical setting remain poorly understood. Outbreaks have been linked to hospital sinks, which have been shown to harbor and, under certain conditions, disperse CPE to surrounding surfaces. Hospital and laboratory studies have proposed that Gram-negative organisms, including CPE, can migrate through plumbing biofilms, leading to widespread contamination of the drainage system. Methods: To assess the prevalence of CPE in hospital sinks, drain swabs and waste trap water samples were taken from 10 sinks in 10 hospitals. Hospitals were in different regions of England; 4 had reported recent cases of CPE infection. To investigate spread and dispersal of CPE, waste traps from a single hospital were installed in a laboratory model sink system. Built to simulate a clinical setting, the model incorporated 12 sinks, 6 of which were connected through a common waste pipe. All 12 taps were automatically flushed. Drainage was automatically controlled. Nutrients were provided daily to maintain the bacterial populations, which were regularly sampled to monitor their composition. At 3 weeks after installation, the waste traps were subjected to a drainage backflow event. Waste trap water populations continued to be monitored, and when transfer between sinks was suspected, isolates were characterized and compared using whole-genome sequencing. Results: Between January and June 2019, 200 samples were taken from 103 sinks. In total, 24 (23%) sinks (in 8 hospitals) harbored CRE; of which 10 (in 5 hospitals) harbored at least 1 CPE. Immediately after a backflow event in the laboratory model system, 2 KPC-producing E. cloacae were recovered from a waste trap in which CPE had not been previously detected. The isolates were identified as ST501 and ST31 and were genetically indistinguishable from those colonizing sinks elsewhere in the system. Following intersink transfer, KPC-producing E. cloacae ST501 successfully integrated into the microbiome of the recipient sink and was detected in the waste trap water at least 6 months after the backflow event. At 2 and 3 months after the backflow, other intersink transfers involving Escherichia coli and KPC-producing E. cloacae were also observed. Conclusions: Sink waste traps and drains are a reservoir for CPE in hospitals. Once established, CPE contamination might not be confined to a single sink and could spread through wastewater plumbing. Hospitals frequently report drainage problems, which could cause or facilitate CPE transfer between sinks and could lead to long-term establishment. Funding: None Disclosures: None